Weight Gain, Mental Symptoms and Self-Esteem in Patients with Schizophrenia - Sevde Öner; Müşerref Didin; İsmail Volkan Şahiner; Havva Gezgin Yazıcı (Psikiyatride Güncel Yaklaşımlar, 2022)
The aim of this study is to examine the weight gain, mental symptoms and self-esteem in patients with schizophrenia undergoing treatment at a community mental health center (CMHC). The study is conducted with 103 schizophrenic patients between 01.08.2021 – 01.02.2022. The data was collected with Personal Information Form, Rosenberg Self-esteem Scale, and Positive and Negative Syndrome Scale (PANSS). 35% of the patients are women, 43.7% are single, and 48.5% are between the ages of 45-64. There was no significant increase between the patients’ weigh measurement value in the first month (x̄=81.185) and the measurement value at the end of six months (x̄=81.320). The decrease in the self-esteem scale mean score at the end of six months (x̄=1.317) was not found significant, when compared to the self-esteem scale mean score in the first month (x̄=1452). The PANSS General Psychopathology subscale mean score was found to be statistically lower at the end of the six-month follow-up (x̄=26.418), compared to the first month mean score (x̄=27.136). There was no significant difference between weight gain, self-esteem, and PANSS positive/negative symptoms in the six-month follow-up of patients with schizophrenia enrolled in CMHC. A significant difference was discovered between the first and sixth-month measurements in PANSS general psychopathology symptoms. It is detected that gender, working status, atypical and mixed antipsychotics use, smoking status, and changes in daytime sleeping habits affect mental symptoms.